Pelatihan Menghitung Anggaran Biaya Atap Rangka Baja Di Kelurahan Sanua Kota Kendari - Masdiana, Masdiana; Sulha, Sulha; Mursidi, Baso; Machmud, Sultan; Arsyad, LM Nurrahmad; M.Rizal, M.Rizal (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2021)
Materials technology have developing rapidly especially since steel is used to replace wood as themain construction material This is not directly proportional to the skills of construction workers.Planning for material requirements and implementing occupational safety (SMK3) when doing workis less. So the Implementing Team carried out training activities at Sanua Sub district, Wesst-KendariDistrict, Kendari City, Southeast of Sulawesi. Team were training on how to calculate the roof trussbudget quickly and easily and they can design the material requirements so which are not materialwasted. The results of the training include increasing knowledge of calculating the cost budget sothat it can compare the cost of using steel which is not too expensive when using wood, especially interms of strength and maintenance and other result was the implementing SMK3 was important whenthey were working. Other results of the training were increased their knowledge of how to planbudgets quicly and Increasing awareness of the implementation of SMK3 is very important.Keywords: Flood adaptive settlement mockups.